Evaluation of Heart Rate Variability in Children with Stutter - Pelin Özcan Ulubeli; Eser Doğan; Mustafa Şahin; Zülal Ülger Tutar; Mehmet Fatih Öğüt (Galenos Yayinevi, 2024)
Aim: The autonomic nervous system has a direct or indirect effect on motor speech and its development. The results of studies evaluating autonomic functions in stuttering individuals show that further research is needed in different age groups. In this study, the aim was to evaluate autonomic function by analysing heart rate variability (HRV) in children with stutter. Materials and Methods: In this study, a total of 41 individuals (11 females, 30 males) between the ages of 6-17 years (mean age: 10.17±2.75), diagnosed with stuttering were evaluated. The control (healthy/normal) group comprised 41 individuals (12 female, 29 male) between the ages of 6-17 years (mean age: 10.78±2.78), who did not have any speech disorder complaints and no family history. The level of stuttering was designated by applying the Turkish version of the Stuttering Severity Instrument Fourth Edition to the diagnosed group. All cases were tested for HRV and analysed using the 24-hour Holter electrocardiography recording method. Correlations between stuttering severity and the HRV parameters of the stuttering group, and correlations of HRV parameters in both groups were examined. Results: A positive significant correlation was found between secondary behaviours in the stuttering group and the standard deviation of the mean NN intervals in 5-minute recordings (SDANN) of the HRV test. Additionally, when the correlation of HRV parameters between the groups was examined, the SDANN parameter in the stuttering group was statistically significantly higher (p<0.05). The other parameters were not statistically significantly different between the groups. Conclusion: In this study, when the HRV parameters of the stuttering children were compared with the non-stuttering children, no significant differences were found to prove autonomic nervous system dysregulation.